Engendering Allograft Ignorance in a Mouse Model of Allogeneic Skin Transplantation to the Distal Hind Limb. Issue 3 (March 2015) - Agarwal, Shailesh; Loder, Shawn; Wood, Sherri; Cederna, Paul S.; Bishop, D. Keith; Wang, Stewart C.; Levi, Benjamin
Abstract : Objective: The aim of this study was to demonstrate lymphatic isolation in a model of hind limb lymph node (LN) excision, consisting of ipsilateral popliteal and inguinal LN excision and to evaluate the immunologic response to allogeneic skin transplanted onto this region of lymphatic isolation. Methods: To study lymphatic flow, C57BL/6 mice underwent lymphadenectomy (n = 5), sham lymphadenectomy (n = 5), or no intervention (n = 5), followed by methylene blue injection. Mice were dissected to determine whether methylene blue traveled to the iliac LN. To study host response to skin transplantation, C57BL/6 mice underwent allogeneic skin transplantation with LN excision (n = 6), allogeneic skin transplantation alone (n = 6), or syngeneic skin transplantation (n = 4). Skin grafts were placed distal to the popliteal fossa and mice were euthanized at day 10. Grafts were stained for endothelial cell and proliferation markers (CD31 and Ki67, respectively). Secondary lymphoid tissues (spleen, ipsilateral axillary LN, and contralateral inguinal LN) were removed and rechallenged with BALB/c alloantigen in vitro with subsequent assay of interferon-γ and interleukin 4 cell expression using ELISPOT technique. Results: Mice that underwent LN excision had no evidence of methylene blue in the iliac nodes; mice without surgical intervention or with sham LN excision consistently had methylene blue visible in the ipsilateral iliac nodes. Mice treated with allogeneic skin transplantation and LN excision had lower expression of interferon-γ and interleukin 4 in the secondary lymphoid tissues. Conclusions: Lymph node excision completely interrupts lymphatic flow of the hind limb. This model of lymphatic isolation impairs the ability of the transplant recipient to acutely mount a Th1 or Th2 response to allogeneic skin transplants. Abstract : Tissue allotransplantation presents a powerful reconstructive option for patients with extremity injuries. However, tissue rejection continues to hinder the utility of this technique. Here, we use a mouse model to demonstrate impaired hind limb lymphatic drainage after lymphadenectomy and evaluate the immunologic response to skin allotransplanted onto the hind limb after lymphadenectomy.